An Analysis of Students’ Difficulties in Reading Comprehension - Septia, Neneng Widya; Indrawati, Indrawati; Juriana, Juriana; Rudini, Rudini (EEdJ: English Education Journal, 2022)
This study was aimed to find out the students’ difficulties in learning reading comprehension at a public high school in Bangka and the factors students have the difficulties. The subject of this study were the students of eighth grade in Bangka. Descriptive qualitative method was used. After the students’ test scores were obtained, then the students’ difficulties were analyzed. After that, the number of difficulties was counted by tabulating and calculating the results. The difficulties faced by the students were difficulty in answering main idea questions (53,67%), vocabulary questions (47,84%), and making inference questions (45,34%). Four factors were found causing the students’ difficulties, those are students’ interest in learning reading because they do not have the desire to read English text and they are not interested in reading. The second factor is students’ difficulties in reading text and translating the English meaning. The third factor is lack of facility in their school since it did not provide enough reading material for them. And the last factor is house environment, the role of a parent at home to give child support is crucial.